Convergence Vs Homogeneity: Exploring Hong Kong’s Identity in Transition - Liu, Xin; Zhang, Yimu (International Journal of Mass Communication, 2025)
This article explores the multiple drivers behind Hong Kong’s identity transition through the lens of the disappearing neon signs. Its cultural and political significances are analyzed through the theoretical frameworks of identity politics, decolonization, and nationalism. The simultaneous forces of decolonization and mainlandization largely accounts for the intricate politicalization of many issues in Hong Kong, including its iconic neon signs, whose connotations has gone through several transitions: from being historical (Western influence), to economic (as a prosperous entrepot and shopping paradise), cultural (unique hybrid of glocalization), technological (becoming outdated in energy efficiency) and even political (fading away after the strengthened regulation in 2010), especially when its early development was a result of bottom-up participation at a grassroots level, while their removal came from a top-down approach through government regulations. The study design incorporates both quantitative and qualitative methods by combining survey results with interviews and policy paper analysis to explore the multiple drivers and the perceived effects on Hong Kong’s identity. This then informs discussions of how to maintain Hong Kong’s position as a space for convergence while developing some new features of in-betweenness.